2019
DOI: 10.1002/jbmr.3804
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Finite Element Models Accurately Predict Subject-Specific and Velocity-Dependent Kinetics of Sideways Fall Impact

Abstract: The majority of hip fractures in the elderly are the result of a fall from standing or from a lower height. Current injury models focus mostly on femur strength while neglecting subject-specific loading. This article presents an injury modeling strategy for hip fractures related to sideways falls that takes subject-specific impact loading into account. Finite element models (FEMs) of the human body were used to predict the experienced load and the femoral strength in a single model. We validated these models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…De Bakker et al (2009) reported 7 neck fractures and 5 intertrochanteric fractures. Interestingly, Fleps et al (2019) also reported a similar distribution of fracture types (11 bones, 3 non-fractures, 3 intertrochanteric, 1 basicervical, 1 subcapital, 3 pelvic) using a more complex and biofidelic setup that included pelvis compound and soft tissue mimicking in a drop test. aBMD at the femoral neck was a good predictor of peak force (R 2 =0.67, RMSE=739 N, figure 3), consistently with previous literature findings (Rezaei and Dragomir-Daescu, 2015).…”
Section: Discussionmentioning
confidence: 76%
“…De Bakker et al (2009) reported 7 neck fractures and 5 intertrochanteric fractures. Interestingly, Fleps et al (2019) also reported a similar distribution of fracture types (11 bones, 3 non-fractures, 3 intertrochanteric, 1 basicervical, 1 subcapital, 3 pelvic) using a more complex and biofidelic setup that included pelvis compound and soft tissue mimicking in a drop test. aBMD at the femoral neck was a good predictor of peak force (R 2 =0.67, RMSE=739 N, figure 3), consistently with previous literature findings (Rezaei and Dragomir-Daescu, 2015).…”
Section: Discussionmentioning
confidence: 76%
“…The models also showed good agreement with low height impact experiments performed with young volunteers, which supports their validity across impact velocities. 17 The fall posture of the subjects was not changed with respect to the impact angles. Although we consider the current posture as realistic for all simulated impact angles, it is likely that fall postures will vary between fall direction and impact angles in real life, with certain trends being common for certain fall and impact directions.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we validated subject-specific finite element (FE) models which allow for the simulation of falls to the side. 17 These models accurately represented ex vivo fall simulations with respect to impact force (RMSE = 10.7%), stiffness (RMSE 12.9%), and fracture outcome (10 out of 11). Furthermore, these FE models allow for the analysis of internal forces 15 and falls with different impact conditions.…”
Section: Introductionmentioning
confidence: 87%
“…2 Other studies 4,32 focused specifically on the fall dynamics, showing that the hip load at touch down is a function of body anthropometry (height and weight), stiffness of the hip, the nearby soft-tissues, the pelvis and the floor. Yet, to the best of the authors' knowledge, only a few studies have replicated hip fractures in vitro by accounting for variations of body fall dynamics and compliance of the soft tissues surrounding the hip, [16][17][18][19] showing that the compliance of the soft tissues surrounding the hip is an important co-factor for the risk of fracture of the hip. 19 Here, we hypothesize that variations of body anthropometry, conjointly with the bone strength, determine the risk of hip fracture.…”
Section: Introductionmentioning
confidence: 99%